Pengaruh Layanan Konseling Kelompok Teknik Self Management Terhadap Motivasi Berprestasi Siswa - Irma Nasyhihati (Journal of Education Counseling, 2025)
Achievement motivation plays an important role in the success of the learning process. Special tips are needed to maintain or even increase achievement motivation. This study aims to determine the effect of group counseling with self-management techniques on students' achievement motivation. The method used is an experiment on one group taken from certain criteria. The hypothesis test used is the Wilcoxon signed rank test. The results of data analysis show that Asymp.Sig (2-tailed) 0.042 <0.005. This shows that there is a significant effect of providing treatment using self-management techniques on students' achievement motivation. Several factors that influence achievement motivation include the physical environment in the form of body shape, parenting patterns such as military and democratic, social levels including status in society, and economic factors.